dan Fungsi Musik Pengiring Tari Kembang Mahameru dalam Kajian Etnomusikologi - Wahyu Paskabahakti (Jurnal Pendidikan Sendratasik, 2026)
This study examines the structural presentation and functions of the musical accompaniment of Tari Kembang Mahameru from an ethnomusicological perspective. Tari Kembang Mahameru is a performing art from Lumajang Regency, East Java, inspired by the grandeur of Mount Semeru that blends East Javanese gamelan tradition with jaranan musical elements. This research employs a descriptive qualitative approach, with audiovisual recordings of the performance at the 2016 East Java Dance Festival accessed via YouTube as the primary data source. Analysis was conducted through repeated audiovisual observation and computational analysis of audio intensity data (RMS) using FFmpeg software. The results show that the musical accompaniment structure is divided into four main sections: introduction (0:00–1:34), development (1:34–2:52), climax (2:52–5:19), and closing (5:19–6:46). Each section has distinct musical characteristics through changes in tempo, rhythm, dynamics, and instrumentation including balungan, kendang, gong, jaranan trumpet, and vocals. Based on Merriam's (1964) theory of music functions, the accompaniment performs six dominant functions: emotional expression, aesthetic enjoyment, entertainment, communication, symbolic representation, and physical response. The close relationship between musical changes and dance movements is realized through the concept of wirama in Javanese performance aesthetics. This study contributes to the documentation and preservation of East Javanese traditional performing arts.   Keywords: ethnomusicology, music function, music structure, Kembang Mahameru Dance, traditional dance accompaniment